(untitled) (Ames, Iowa, 2008)
Environmental Best Management Practices for Aquaculture will provide technical guidance to improve the environmental performance of aquaculture. This book will be the only comprehensive guide to BMPs for mitigation of environmental impacts of aquaculture in the United States. The book addresses development and implementation of BMPs, BMPs for specific aquaculture production systems, and the economics of implementing best management practices. Written by internationally recognized experts in environmental management and aquaculture from academia, government, and non-governmental organizations, this book will be a valuable reference for innovative producers, policy makers, regulators, research scientists, and students.
Keywords: Aquaculture,Fishery management; Environmental aspects